2021
DOI: 10.1108/rpj-11-2020-0274
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric indicators analysis of additive manufacturing research trends from 2010 to 2020

Abstract: Purpose Although many researchers have widely studied additive manufacturing (AM) as one of the most important industrial revolutions, few have presented a bibliometric analysis of the published studies in this area. This paper aims to evaluate AM research trends based on 4607 publications most cited from year 2010 to 2020. Design/methodology/approach The research methodology is bibliometric indicators and network analysis, including analysis based on keywords, citation analysis, productive journal, related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 150 publications
0
4
0
Order By: Relevance
“…To gain a thorough understanding of the evolution of this research field from 2002 to 2022, this study will conduct a scientometric evaluation and analysis of the papers pertaining to the multi-material additive manufacturing of engineered lattice structures. The scientometric review is also qualitatively validated by comparing the present data with other bibliometric studies on AM [ 38 , 39 , 40 , 90 , 91 , 92 , 93 ]. An extensive systematic review is then offered to offer deeper insights into the technology and applications of multi-material additive manufacturing of polymers based on the findings of the scientometrics analysis.…”
Section: Methodsmentioning
confidence: 72%
“…To gain a thorough understanding of the evolution of this research field from 2002 to 2022, this study will conduct a scientometric evaluation and analysis of the papers pertaining to the multi-material additive manufacturing of engineered lattice structures. The scientometric review is also qualitatively validated by comparing the present data with other bibliometric studies on AM [ 38 , 39 , 40 , 90 , 91 , 92 , 93 ]. An extensive systematic review is then offered to offer deeper insights into the technology and applications of multi-material additive manufacturing of polymers based on the findings of the scientometrics analysis.…”
Section: Methodsmentioning
confidence: 72%
“…Ahmed et al (2021) perform bibliometric analysis of 3D printing technology to identify new trends, with a particular focus on post-COVID-19 applications. It is also reported that, according to the bibliometric analysis, metal 3D printing emerged as one of the top research areas, with medical applications being particularly highlighted (Jemghili et al , 2021).…”
Section: Literature Review/backgroundmentioning
confidence: 99%
“…VOSviewer [ 85 ] and BibExcel [ 86 ] softwares are used for doing the scientometric-bibliometric analysis. These two softwares have been widely used in recent scientometric-bibliometric studies [ [87] , [88] , [89] , [90] , [91] ].…”
Section: Scientometric and Bibliometric Analysismentioning
confidence: 99%